Entrepreneurship Innovation in Strengthening Economic Security on The Temajuk Border of West Kalimantan Indonesia - Elyta, Elyta; Jamaliah, Jamaliah; Ahmad, Mohammad Zaki (Journal of Government and Civil Society, 2023)
Entrepreneurship is an economic activity carried out by the community on a small to medium scale. Entrepreneurship can involve the community to strengthen the community's economy through income obtained from entrepreneurial products made. However, there is a need for entrepreneurial strategies and innovations to adapt to environmental developments and community needs. This study aims to analyze Entrepreneurial Innovation in Strengthening Economic Security at the Temajuk Border, West Kalimantan, Indonesia, with the latest implementation of community-based entrepreneurship training in the Temajuk border area. This study uses the development method and the type of R&D research with data collection through interviews, observations, and literature studies. The results of this study found that entrepreneurial innovation at the border of Temajuk Sambas, West Kalimantan, Indonesia, carried out with pre-training, implementation, and post-training stages can increase community entrepreneurial knowledge and can strengthen economic security in border communities.Kewirausahaan merupakan kegiatan ekonomi yang dilakukan masyarakat dalam sekala kecil hingga menegah, kewirausahaan dapat melibatkan masyarakat untuk memperkuat perekonomian masyarakat melalui pendapatan yang di dapat dari produk wirausaha yang di buat. Akan tetapi perlu adanya strategi dan inovasi kewirausahaan agar beradaptasi dengan perkembangan lingkungan dan kebutuhan masyarakat. Penelitian ini bertujuan untuk menganalisis Inovasi Kewirausahaan Dalam Penguatan Economy Security Di Perbatasan Temajuk Kalimantan Barat Indonesia dengan keterbaruan yaitu pada pelaksanaan pelatihan kewirausahaan berbasis masyarakat di kawasan perbatasan Temajuk. Penelitian ini menggunakan metode pengembangan dan jenis penelitian R&D dengan pengambilan data melalui wawancara, observasi, dan studi literatur. Hasil penelitian ini menemukan bahwa inovasi kewirausahaan di perbatasan Temajuk Sambas Kalimantan Barat Indonesia dilakukan dengan tahapan pra-pelatihan, pelaksanaan, dan pasca-pelatihan dapat meningkatkan pengetahuan berwirausaha masyarakat dan dapat memperkuat keamanan ekonomi di masyrakat perbatasan.